Avoiding the pocket: A case report of coiling of distal shunt catheter into subcutaneous pocket - Garling, Richard Justin (Int J Surg Case Rep, 2017)
INTRODUCTION: Hydrocephalus is one of the most common disorders of neurosurgery and ventricular shunting, the primary surgical intervention, malfunctions in 85% of patients by 10 years. PRESENTATION OF CASE: Here we present a case of a 12-year-old girl with history of a vagal nerve stimulator (VNS) and ventricular shunt, most recently revised from ventriculoatrial (VA) to ventriculoperitoneal (VP) shunt at an outside hospital. The patient presented with a new left chest bulge, nausea, emesis, and seizures. Imaging revealed the patient’s distal shunt catheter to have completely migrated and coiled into the VNS subcutaneous pocket. Subsequently, the patient’s distal shunt catheter was externalized, and later internalized back to a VA shunt. DISCUSSION: Potential spaces from previous surgeries such as VNS can lead to coiling of distal shunt catheters. In this case, the coiled distal shunt catheter led to hydrocephalus and the patient’s presenting symptoms. CONCLUSION: It is imperative to recognize patients with previous surgeries, especially those involving subcutaneous implants and to avoid passing of distal shunt catheters through these potential spaces.